Limited increase in primary HIV‐1C drug resistance mutations in treatment naïve individuals in Ethiopia. Issue 6 (3rd February 2015) - Huruy, Kahsay; Maier, Melanie; Mulu, Andargachew; Liebert, Uwe G.
<x xml:space="preserve">Abstract</x> Antiretroviral drug resistance is a major challenge for management and control of HIV‐1 infection worldwide and particularly in resource limited countries. The frequency of primary drug resistance mutations (DRMs) and of naturally occurring polymorphisms was determined in 83 antiretroviral treatment (ART) naïve Ethiopian individuals infected with HIV‐1, consecutively enrolled in 2010. In all individuals HIV‐1C was found. The median (interquartile range) of CD4+ T‐cell count and viral load were 100 (49–201) cells/μl and 44, 640 (12, 553–134, 664) copies/ml, respectively. Protease (PR) and reverse transcriptase (RT) genes of HIV‐1 RNA were amplified and sequenced. The proportion of primary DRM to any drug class, using the World Health Organization mutation lists, was 7.2% (6/83), thus exceeding the WHO threshold limit of 5%. Three individuals (3.6%) had non‐nucleoside reverse transcriptase inhibitor (NNRTI) mutations, two individuals (2.4%) had protease inhibitor mutations, and one (1.2%) had mutations associated with two drug classes (nucleoside reverse transcriptase inhibitor and NNRTI). In addition, the frequency of polymorphisms in the PR and RT genes was higher compared with previous studies in Ethiopian as well as worldwide isolates. Hence, genotypic drug resistance testing as part of routine management of individuals seems reasonable even in resource limited countries prior to treatment in order to allow proper choice of ART. J. Med. Virol. 87:978–984, 2015. © 2015 Wiley Periodicals, Inc.